What's Hot in Evolutionary Computation - Friedrich, Tobias; Neumann, Frank (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
We provide a brief overview on some hot topics in the area of evolutionary computation. Our main focus is on recent developments in the areas of combinatorial optimization and real-world applications. Furthermore, we highlight recent progress on the theoretical understanding of evolutionary computing methods.